Şah Veliyyullah ed-Dihlevî ve Dihlevîlik - Aydın, Ahmet (My University, 2012)
Bu çalışma fıkıh ilmi merkezinde Şah Veliyyullah ed-Dihlevî’nin (v. 1762) ihyâ düşüncesini tanımlamayı ve Dihlevîlik kavramı altında, onun etrafında gelişen bir ilim çevresi ve ihyâ hareketinin varlığını ortaya koymayı hedeflemektedir.

This study aims to present an analysis of the idea of ''revival'' (Ihya) in the works of Shah Wali Allah Dihlawi (d.1762), the emergence of the concept of Dihlawiya and its impact on the Islamic Fıqh scholarship.
Keywords: İslam Hukuku